The Limits of Central Counterparty Clearing: Collusive Moral Hazard and Market Liquidity - Thorsten V. Koeppl (Queen's University, Department of Economics, 2013)
Can central counterparty (CCP) clearing control counterparty risk in the presence of risk taking that can aggravate such risk? When counterparty risk is not observable, I show that central clearing leads to higher collateral requirements for two different reasons. Without collusion about risk taking, a CCP offering diversification of risk cannot selectively forgo incentives for transactions that use collateral only for insurance. With collusion about risk taking, a CCP needs to charge collateral in line with the worst counterparty quality to control risk taking. Requiring more collateral reduces market liquidity and worsens incentives causing a feedback effect that amplifies collateral costs.
Keywords: G32; G38; D82; D83; 330; CCP Clearing; Counterparty Risk; Moral Hazard; Collateral; Market Liquidity